2010
DOI: 10.1016/j.jcrs.2010.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser in laser in situ keratomileusis

Abstract: Flap creation is a critical step in laser in situ keratomileusis (LASIK). Efforts to improve the safety and predictability of the lamellar incision have fostered the development of femtosecond lasers. Several advantages of the femtosecond laser over mechanical microkeratomes have been reported in LASIK surgery. In this article, we review common considerations in management and complications of this step in femtosecond laser–LASIK and concentrate primarily on the IntraLase laser because most published studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 78 publications
3
72
0
4
Order By: Relevance
“…However, the biological safety of the 1053-nm wavelength of the iFS laser has been well established. [57][58][59][60] Additionally, the relatively short illumination time also eliminates the possibility of mutagenesis or altered retina cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological safety of the 1053-nm wavelength of the iFS laser has been well established. [57][58][59][60] Additionally, the relatively short illumination time also eliminates the possibility of mutagenesis or altered retina cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafast femtosecond laser (FSL) technology was introduced in 2001, 8 revolutionising corneal flap creation in laser in situ keratomileusis (LASIK). This has resulted in more predictable and accurate flaps with a lower frequency of complications.…”
Section: Lasers In Cataract Surgerymentioning
confidence: 99%
“…Cataract surgery is being transformed into a refractive operation, and is now the most common procedure to correct refractive errors, being performed five times more frequently than corneal refractive treatments. 8 Unfortunately, the limitations of currently available biometry and surgical techniques mean that the full potential of toric, multifocal, and accommodating IOLs may not reliably be achieved. Several authors have suggested that FLACS may provide the solution to this dilemma, as well as improving the results of standard cataract surgery, which are highly dependent on the skill and experience of the surgeon.…”
Section: The Shifting Of Patient Expectationsmentioning
confidence: 99%
“…The microkeratome coupled to the artificial chamber can produce an endothelial donor lamella (EDL); however, the cutting irregularities and the unpredictability of the depth of the cut are major impediments to the visual outcome of lamellar transplantation (3,4) . New models of femtosecond lasers (FS) produce a better corneal lamella quality than the microkeratome (5)(6)(7)(8)(9) . Lasers with a high frequen cy and low energy tend to make a corneal cut smoother, more homogeneous, accurate, and reproducible, as smaller intrastromal bubbles are produced, creating smaller cavities in the cornea (5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…New models of femtosecond lasers (FS) produce a better corneal lamella quality than the microkeratome (5)(6)(7)(8)(9) . Lasers with a high frequen cy and low energy tend to make a corneal cut smoother, more homogeneous, accurate, and reproducible, as smaller intrastromal bubbles are produced, creating smaller cavities in the cornea (5)(6)(7)(8)(9) . Cell necrosis and inflammation in the cornea increase as the energy used by FS increases (5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%